Speciation of As in environmental samples using the nano-TiO2/PCHG-FAAS online system. Issue 11 (19th September 2017) - Pinheiro, Bianca S.; Gimenes, Luana L.; Moreira, Ailton J.; de Araújo, André F.; Freschi, Carolina D.; Freschi, Gian Paulo Giovanni
ABSTRACT: This work presents an alternative method for arsenic speciation using the nano-TiO2 hydride generation photocatalytic hydride generation (PCHG) system, which is easily separated from the medium. Nano-TiO2 was studied as photocatalyst to reduction of arsenic species by UV-induced with formic acid and atomic absorption detection of different forms of arsenic [As (III), As (V), dimethylarsinic acid (DMA)] in environmental samples (water, sediment and plant). The effect of the average pH, the organic acid concentration, the ultraviolet irradiation time and their amount were investigated. With the presence of formic acid, the process was more effective in the reduction of arsenic when compared to other organic acids, mainly acetic acid. In addition, the photocatalytic hydride generation and flame atomic absorption spectrometry (nano-TiO2 /PCHG-FAAS) increased the identification and quantification of different arsenic species. The ultrasound extraction procedure was used as a method to prepare samples with solutions of 1.0 mol L −1 phosphoric acid. The accuracy of the measurements (n = 12), calculated as relative standard deviation, was less than 8.6%. The detection limits for As (III) and As (total) in samples were 0.418 and 0.574 μg g −1, respectively.